Bonhoeffer e a neoteocracia: Uma crítica à aproximação entre os "evangélicos" e a direita brasileira = Bonhoeffer and the neo-theocracy: A critique of the alignment between “evangelicals” and the Brazilian right - Kuzma, Cesar Augusto; Machado, Filipe Costa (2024)
In recent years, it has been possible to see a growth in the number of Evangelical candidates and the space they occupy in parliamentary benches. Thus, there was - and still is - a political movement that identifies itself as the right wing and as a Christian that tries to dominate the government to establish what João Décio Passos calls neo-theocracy, which is, the government of a religious leader who represents the divine. This phenomenon has three main beliefs: a Pantocrator God, a war between good and evil, and the mythological leader. These aspects were also perceived in Nazi Germany and, therefore, Bonhoefferian criticism resurfaces as a necessary voice for current Brazil. In the face of the Pantocrator God, Bonhoeffer argues that one must live in the world in which God seems not to be; in a warlike and dual perspective, Christ is the center of all creation; finally, the mythological leader is nothing more than a seducer who wants to occupy the throne of the Nazarene. Through bibliographical research, this article aims to present Dietrich Bonhoeffer's criticism of the rapprochement between religion and politics, observed here in the context of the 2018 Brazilian elections, in the perception of an alignment between the Brazilian right and the "evangelicals", with consequences for democracy in the following years.
Nos últimos anos, foi possível perceber um crescimento do número de candidatos evangélicos e do espaço que eles ocupam nas bancadas parlamentares. Sendo assim, houve - e ainda há - um movimento político que se identifica como direita e como cristã que tenta dominar o governo para instaurar o que João Décio Passos chama de neoteocracia, isto é, o governo de um líder religioso que representa o divino. Este fenômeno tem três crenças principais: um Deus pantocrator, uma guerra entre o bem e o mal e um líder mitológico. Estes aspectos também foram percebidos na Alemanha nazista e, por isso, a crítica bonhoefferiana ressurge como uma voz necessária para o Brasil atual. Diante do Deus pantocrator, Bonhoeffer argumenta que se deve viver no mundo em que Deus parece não estar; em uma perspectiva bélica e dual, Cristo é o centro de toda criação; por fim, o líder mitológico não passa de um sedutor que deseja ocupar o trono do Nazareno. Por meio de uma pesquisa bibliográfica, o presente artigo tem por objetivo apresentar a crítica de Dietrich Bonhoeffer à aproximação entre religião e política, observada aqui no contexto das eleições brasileiras de 2018, na percepção de um alinhamento entre a direita brasileira e os "evangélicos", com consequência para a democracia nos anos seguintes.
Keywords: Dietrich Bonhoeffer; Direita Brasileira; João Décio Passos; Neoteocracia